2008
DOI: 10.1016/s1472-6483(10)60288-x
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation induction with tamoxifen and alternate-day gonadotrophin in patients with thin endometrium

Abstract: Tamoxifen has been reported to be oestrogenic on the lower genital tract. To evaluate its potential positive effect on the endometrium, and consequently early miscarriage and ongoing pregnancy rate, a prospective study was employed in patients for intrauterine insemination who failed to develop an adequate endometrial thickness in a previous ovulatory cycle. Ovarian stimulation was initiated with tamoxifen 40 mg/day from day 3 of the menstrual cycle for 7 days or clomiphene 100 mg/day for 5 days, in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Intra-uterine insemination is practicing widely as an empirical treatment for male factor infertility and as a mean to bypass defects in sperm-cervical mucus interaction [18]. In the present study IUI was performed for 152 couples with mild male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-uterine insemination is practicing widely as an empirical treatment for male factor infertility and as a mean to bypass defects in sperm-cervical mucus interaction [18]. In the present study IUI was performed for 152 couples with mild male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
“…An increment in the duration of infertility to more than 10 years results in reduction in the testicular blood supply especially in the older infertile males and this affects the normal physiology of the testes and epididymis which results in marked elevation of the serum FSH and LH levels [27]. Furthermore there is an increase in the number of pathological spermatozoa which linked to an increase in both age and duration of infertility [18]. Therefore, in this study least positive IUI with 10 years duration of infertility and age ≥ 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of clinical pregnancy was significantly higher in the 20-39-min group (18.3%) than in the 0-19-, 40-59-, and 60-80-min groups (12.7, 11.4 and 9.1%) (all P \ 0.05). The (10-20) 9 10 6 group achieved a remarkably higher pregnancy rate (16.7%) than the (0-9), (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and [ 30 9 10 6 groups (0, 11.4, and 8.3%) (all P \ 0.05). Logistic multivariate analysis showed that the rate of clinical pregnancy was decreased with the increased age of the women (OR 0.89, 95% CI 0.83-0.94) but significantly elevated in the 20-39-min group (OR 2.11, 95% CI 1.34-3.13) and of (10-20) 9 10 6 group (OR 2.06, 95% CI 1.32-3.46).…”
Section: Discussionmentioning
confidence: 88%
“…gonadotropins, or gonadotropins alone in terms of comparable if not higher CPR/cycle and take home baby rates. Significantly higher serum levels of LH, endometrial thickness, and progesterone at the time of hCG administration have been observed despite a significantly lower serum E2 level [29][30][31] with significantly lower costs, risks, and patient inconvenience in patients with unexplained infertility [29,30,32,33] endometriosis, and combined indications [34], and lower FSH dose requirement and IUI cancelation rates in patients with ovulatory infertility [35] and older infertile women [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation